Metabotropic glutamate receptor-1 regulates inflammation in triple negative breast cancer. Issue 1 (December 2018) - Sexton, Rachel; Hachem, Ali; Assi, Ali; Bukhsh, Miriam; Gorski, David; Speyer, Cecilia
Abstract Breast cancer remains a major cause of death among women. 15% of these cancers are triple negative breast cancer (TNBC), an aggressive subtype of breast cancer for which no current effective targeted therapy exists. We have previously demonstrated a role for mGluR1 in mediating tumor cell growth, endothelial cell proliferation, and tumor-induced angiogenesis in TNBC. In this study, we explore a role for mGluR1 in regulating inflammation in TNBC.GRM1 expression was silenced in MDA-MB-231 cells to study changes in expression of inflammatory genes regulated by mGluR1. Results were confirmed by ELISA usingGRM1 -silenced and overexpressed cells and mGluR1 inhibitors. A functional role for these differentially expressed genes was determinedin vitro andin vivo . 131 genes were differentially expressed inGRM1 -silenced MDA-MB-231 cells, with some of these falling into four major canonical pathways associated with acute inflammation, specifically leukocyte migration/chemotaxis. Upregulation of three of these genes (CXCL1, IL6, IL8 ) and their corresponding protein was confirmed by qPCR analysis and ELISA inGRM1 -manipulated TNBC cells. Upregulation of these cytokines enhanced endothelial adhesion and transmigration of neutrophils in co-culture assays and in 4T1 mouse tumors. Our results suggest mGluR1 may serve as a novel endogenous regulator of inflammation in TNBC.